Temperature and Humidity Distribution Study of Mocaf Chip Hybrid Dryer - Susilo, Bambang; Okaryanti, Rahartina W. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Hybrid dryer is a dryer that uses two or more sources of energy for the evaporation. Hybrid dryer in this experiment use solar energy and biomass energy. This technology is an alternative technology for drying of agricultural products. The purpose of this study is to examine the technical parameters associated with the hybrid dryer include changes in temperature and the distribution of temperature and RH, based on natural convection and forced convection using mechanical fan. The performance test of both method starts at 09.00 pm until 18.00 pm. Data taken every 1 hour includes temperature in the dryer, temperature of wet bulb and dry bulb, and the speed of wind. Materials used in this study is Mocaf fermentation chips with 1-1.5 mm thickness. The result of the research shows that the dryer with solar energy with force convection has the best performance. The temperature of this hybrid dryer spreads in the range between 33.2 °C and 34.2 °C and the Relative humidity (RH) spreads between 33.8% and 53.5%. The temperature and RH distribution of hybrid dryer machine with natural convection of solar energy was relative low. The temperature spreads between 28 °C and 31.9 °C, and the relative humidity spreads between 37.85% and 54.6%. Light intensity during drying with sun-heat was 400.7 lux and wind velocity was 0.16 m/s.The hybrid dryer with electrical fan was better than that without fan. Hybrid dryer still need electrical energy input to generate forced convection. Keywords: hybrid dryer, light intensity, temperature, humidity, water content